Impact of Endurance Exercise Training on Biomarkers of Aortic Endothelial Damage in Diabetic Rats - Mahtab Fouladi; Maryam Mahmoudabady; Zahra Gholamnezhad; Sadegh Shabab; Saeed Niazmand; Hossein Salmani (Cardiovascular Therapeutics)
Given the heightened risk of diabetes-related cardiovascular events associated with inactivity, this study investigates the molecular mechanisms of vascular damage in streptozotocin (STZ)-induced diabetic rats. The aim is to elucidate the impact of different exercises (interval and continuous training) and metformin on biochemical parameters, aortic injury, oxidative stress, and inflammation to provide insights into potential therapeutic interventions for diabetes-associated vascular complications. Male Wistar rats were administered a single dose of STZ (60 mg/kg) to induce diabetes. Diabetic rats underwent either interval training or continuous training (40 min/day, 5 days/week, 6 weeks), received metformin (300 mg/kg), or a combination of metformin and exercise. After 6 weeks, biochemical parameters in serum and oxidative stress markers and mRNA expression of endothelial nitric oxide synthase (eNOS), lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1), and intercellular adhesion molecule-1 (ICAM-1) in aorta tissue were assessed. Serum levels of fasting blood sugar (FBS), triglyceride (TG), total cholesterol (TC), low-density lipoprotein (LDL), TG/HDL, TC/HDL, and LDL/HDL ratios were significantly reduced in all treatment groups compared to the diabetes group. Both types of exercises, metformin, and exercise+metformin combinations, significantly reduced oxidative stress by decreasing malondialdehyde (MDA) and enhancing the antioxidant status in the aortic tissue compared to the diabetic group. In addition, in exercise groups, metformin, and combination groups, the expression of eNOS was significantly elevated, while LOX-1 and ICAM-1 expression significantly decreased compared to the diabetic group. In most cases, the combination of exercise and metformin (especially interval training) was more effective than exercise alone. It seems that exercise along with taking metformin can be considered as a therapeutic method by improving hyperglycemia and hyperlipidemia and reducing oxidative stress and vascular inflammatory responses, leading to ameliorating biomarkers function related to endothelial damage in experimental diabetes conditions.